2007
DOI: 10.1152/ajpcell.00611.2005
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically stimulated osteocytes regulate osteoblastic activity via gap junctions

Abstract: The strong correlation between a bone's architectural properties and the mechanical forces that it experiences has long been attributed to the existence of a cell that not only detects mechanical load but also structurally adapts the bone matrix to counter it. One of the most likely cellular candidates for such a "mechanostat" is the osteocyte, which resides within the mineralized bone matrix and is perfectly situated to detect mechanically induced signals. However, as osteocytes can neither form nor resorb bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
137
1
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(155 citation statements)
references
References 46 publications
9
137
1
4
Order By: Relevance
“…Note that the fluid flow to which osteocytes were exposed in this study is 2 hours. Several others studies (1,16,50,51,57) have shown that mechanical stimuli at this duration can induce many changes in markers of bone formation/resorption in bone cells. We expect that with longer flow exposure times, the bone resorption inhibition effect from mechanical loading might be further enhanced.…”
Section: Discussionmentioning
confidence: 99%
“…Note that the fluid flow to which osteocytes were exposed in this study is 2 hours. Several others studies (1,16,50,51,57) have shown that mechanical stimuli at this duration can induce many changes in markers of bone formation/resorption in bone cells. We expect that with longer flow exposure times, the bone resorption inhibition effect from mechanical loading might be further enhanced.…”
Section: Discussionmentioning
confidence: 99%
“…Currently the inhibitory pathway via sclerostin receives a lot of attention, but there are also several studies pointing to stimulatory pathways (Heino et al 2004;Imai et al 2009;Tatsumi et al 2007;Taylor et al 2007;Vezeridis et al 2006). Tatsumi et al (2007) were able to specifically kill 70-80% of osteocytes in mice, via a toxin that did not directly affect other bone cells; although they observed a marked decrease in sclerostin mRNA, they did not observe an increase in osteoblast activity, which lead them to suggest that "it is conceivable that in addition to negative regulators such as sclerostin, one or more positive regulators are produced by osteocytes".…”
Section: Discussionmentioning
confidence: 99%
“…Tatsumi et al (2007) were able to specifically kill 70-80% of osteocytes in mice, via a toxin that did not directly affect other bone cells; although they observed a marked decrease in sclerostin mRNA, they did not observe an increase in osteoblast activity, which lead them to suggest that "it is conceivable that in addition to negative regulators such as sclerostin, one or more positive regulators are produced by osteocytes". Taylor et al (2007) co-cultured osteocytes exposed to fluid flow with osteoblasts shielded from this flow but connected to the osteocytes via gap junctions: fluid flow on osteocytes led to increased alkaline phosphatase activity in osteoblasts, but not if gap junctions were blocked. This indicates that there was a stimulatory signal reaching the osteoblasts via gap junctions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These conditional Cx43 knockout mice, which use a 2.3-kb collagen I promoter-driven Cre-recombinase to excise a floxed Cx43 allele in cells of the osteoblast lineage, exhibit severe osteopenia as a result of defective osteoblast function. Further, the skeletons of these animals have been shown to be refractory to the anabolic effects of intermittent PTH administration, indicating a critical role of Cx43 in coordinating cell function in response to anabolic cues.Relatively little is known about the precise molecular role of gap junctions in sensing and responding to biological cues during bone formation, though in the past decade critical insights have been gained into the importance of gap junctions in processes such as response to growth factors and hormones (Schiller et al, 1992;Chiba et al, 1994;Van der Molen et al, 1996;Civitelli et al, 1998;Schiller et al, 2001), mechanical load (Jorgensen et al, 1997(Jorgensen et al, , 2000Ziambaras et al, 1998;Romanello and D'Andrea, 2001;Saunders et al, 2001Saunders et al, , 2003Cherian et al, 2003Cherian et al, , 2005Taylor et al, 2007), bisphosphonates (Plotkin et al, 2002(Plotkin et al, , 2005, and interaction with other cells (Villars et al, 2002). Importantly, less still is known regarding the biologically relevant second messengers that osteoblast and osteocyte gap junctions communicate among cells, and many molecular mechanisms have yet to be deduced.…”
mentioning
confidence: 99%